Study On The Relationship Between Sulfate Reduction Pathways And Dormancy Of Microbulbifer Aggregans (Ccb-Mm1) - Tarmizi, Diyana (2021)
Dormancy is a way for bacteria to survive in unfavourable conditions such as nutrient starvation, very high temperature and desiccation, and toxin presence in the environment. Although genetic and metabolic regulations of dormancy for pathogens are well understood, metabolic regulation for marine bacteria entering dormancy is scarcely studied. Microbulbifer aggregans sp. CCB-MM1 isolated from estuarine sediment of Matang Mangrove Forest, Perak, Malaysia, possesses rod-coccus cell cycle in which coccus cell is its dormant form. Furthermore, it shows cell aggregation before changing cell morphology to coccus and has ability to degrade polysaccharide such as starch. RNA-sequencing (RNA-seq) analysis of CCB-MM1 revealed that atpD from ATP synthase Operon II (ASOII) together with sulfite reductase gene of dissimilative sulfate reduction pathway, asrA were highly expressed whereas sulfite reductase gene of assimilative sulfate reduction pathway, cysI was suppressed in dormant state. Based on that information, this study was conducted with the aim to investigate the relationship between sulfate reduction pathways and dormancy of CCB-MM1. The atpD, asrA, and cysI disruption mutants were constructed and cultured in four different media which were modified 0.1 % high nutrient artificial seawater medium (H-ASWM) broth with and without MgSO4 and modified artificial seawater (ASW) with and without MgSO4.